Effect of bull performance on progeny early growth and genetic relationships between bull and progeny traits - Aktar, S; Bhuiyan, AKFH; Saha, NG; Hoque, MA (Bangladesh Journal of Animal Science, 2012)
Records on four bulls and 96 of their progeny born from 2005 to 2011 with pedigree information were used to estimate the impact of bull performance on progeny early growth and the genetic relationships between traits of bull and their progeny. Traits included in this study were metabolic body weight, feed intake and residual feed intake (RFI) for bull performance and birth weight and average daily gain for progeny performance. The variance and covariance components were estimated by the REML method with the VCE computer program. The metabolic body weight of breeding bulls ranged from 92.88±1.22 to 106.05±2.28 kg. The average daily feed intake of breeding bulls differed significantly (p<0.05). The RFI of breeding bulls were ranged from -0.57±0.07 to 0.54±0.06 kg/day. It has been found that the RFI values of two bulls were negative and the other two bulls were positive. The mean values for birth weight of calves produced from different breeding bulls ranged from 16.15±2.01 to 17.71±1.89 kg. Effects of breeding bulls on birth weight and average daily gain of male calves were highly significant (p<0.01). Mean values for birth weight and average daily gain of female calves were affected also significantly (p<0.05) among breeding bulls. Estimated heritability for birth weight was moderate (0.30) and for average daily gain was low (0.26). The genetic correlation between metabolic body weight of bulls and birth weight of their progeny was strong (rg=0.52), whereas feed intake of bulls with birth weight and average daily gain of their progeny were moderate (0.43±0.21 and 0.40±0.23, respectively). Low but favorable negative genetic correlation (rg=-0.10) was observed between RFI of bulls with average daily gain of their progeny. Estimated moderate heritability indicated that variation exist on average daily gain of calves. The negative genetic correlation between RFI of bulls and average daily gain of their progeny indicated that it was possible to improve simultaneously RFI of breeding bulls and daily gain of their progeny. DOI: http://dx.doi.org/10.3329/bjas.v40i1-2.10620 Bang. J. Anim. Sci. 2011. 40 (1-2): 1-7